ChemInform Abstract: Enhanced Photoresponsive Ultrathin Graphitic‐Phase C3N4 Nanosheets for Bioimaging. Issue 20 (25th April 2013) - Zhang, Xiaodong; Xie, Xiao; Wang, Hui; Zhang, Jiajia; Pan, Bicai; Xie, Yi
Abstract Ultrathin graphitic‐phase C3N4 nanosheets are prepared by a liquid exfoliation route from bulk C3N4 in water.